Решите уравнения 1) x^2+3x-(1-2x^2)=3x^2-x+4 2) x^2-5x+5=-x^2-x-(-3-2x^2) 3)-2x^2+4x-7=-x^2+2x-(x^2-3)

Решите уравнения 1) x^2+3x-(1-2x^2)=3x^2-x+4 2) x^2-5x+5=-x^2-x-(-3-2x^2) 3)-2x^2+4x-7=-x^2+2x-(x^2-3)
Гость
Ответ(ы) на вопрос:
Гость
N 1 X^2 + 3x - ( 1 - 2x^2 ) = 3x^2 - x + 4 X^2 - 3x - 1 + 2x^2 = 3x^2 - X + 4 3x^2 - 3x - 1 = 3x^2 - X + 4 - 3x + X = 4 + 1 - 4x = 5 X = - 1,25 ОТВЕТ ( - 1,25 ) N 2 X^2 - 5x + 5 = - x^2 - x - ( - 3 - 2x^2 ) X^2 - 5x + 5 = - x^2 - X + 3 + 2x^2 X^2 - 5x + 5 = x^2 - X + 3 - 5x + X = 3 - 5 - 4x = - 2 X = 0,5 ОТВЕТ 0,5 N 3 - 2x^2 + 4x - 7 = - x^2 + 2x - ( x^2 - 3 ) - 2x^2 + 4x - 7 = - x^2 + 2x - x^2 + 3 - 2x^2 + 4x - 7 = - 2x^2 + 2x + 3 4x - 2x = 3 + 7 2x = 10 X = 5 ОТВЕТ 5
Не нашли ответ?
Ответить на вопрос
Похожие вопросы